A GNR no comando de operações de socorro - Lopes, José Manuel Ferreira (2022)
The Civil Protection activity is part of what is one of the fundamental tasks of the State: Security. The responsibility for the development of this activity lies largely with the National Authority for Emergency and Civil Protection (ANEPC), which has been constituted over the last few years, as the pillar of the entire structure of protection and assistance in Portugal, responsible for its implementation and operation. In this context, the Integrated Protection and Rescue Operations System (SIOPS) is of great importance, operated through a structure that sought to identify, integrate and coordinate the performance of the various actors in civil protection actions. In this system, its most operational aspect is highlighted, in which the Operations Management System (SGO) and the Commander of Relief Operations (COS), which is a technically qualified element with the authority to assign missions, articulate the forces assigned to it, direct and regulate logistical aspects of immediate interest to the operations, as well as manage the operational information. Given the diversity of scenarios that can be classified as occurrences in the scope of civil protection, it is important to adapt the exercise of the COS function, with the technical qualification for the management of operations in the theater of operations (TO) and not just, as it tends to be verified, for the management of tasks inherent to the provision of direct help to victims, which is considered excessively reductive. In this regard, it is important to highlight the role of the GNR, as a Civil Protection Agent (APC), for which, helping and assisting the population has been a mission historically assigned, which is why, in several scenarios, it is the APC better qualified to assume the command of relief operations.